2022
DOI: 10.1186/s12905-022-02061-w
|View full text |Cite
|
Sign up to set email alerts
|

Level of women-friendly care provision among mothers in immediate post-partum period at public hospitals of Southeast Ethiopia: a cross-sectional study

Abstract: Background The women-friendly care approach focuses on women’s rights to have access to quality care for themselves as individuals, as mothers, and for their infants. However, access to quality health services is not guaranteed for many women, particularly in low and middle-income countries. Hence, this study aimed to assess the level of women-friendly care provision and associated factors among mothers in the immediate post-partum period at public hospitals of Bale Zone, Southeast Ethiopia 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
1
3
1
Order By: Relevance
“…Our study revealed that the primiparous participants were 2.30 times more likely to receive friendly care than women who had a parity ≥4. These findings are consistent with those of a study conducted in Southeast Ethiopia ( 12 ). A possible explanation for our findings could be that primipara mothers might consider the healthcare setting unfamiliar and believe the quality of the care provided by the facility to be perfect, while multipara mothers have had experience with the facility's care and have rated its services accordingly.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our study revealed that the primiparous participants were 2.30 times more likely to receive friendly care than women who had a parity ≥4. These findings are consistent with those of a study conducted in Southeast Ethiopia ( 12 ). A possible explanation for our findings could be that primipara mothers might consider the healthcare setting unfamiliar and believe the quality of the care provided by the facility to be perfect, while multipara mothers have had experience with the facility's care and have rated its services accordingly.…”
Section: Discussionsupporting
confidence: 93%
“…This result is higher than those of 61% of the studies conducted in the Bale Zone in Southeast Ethiopia ( 12 ). This discrepancy might be due to the use of different measurement tools and study settings, the research for the Kene et al (2022) study was carried out solely at a public hospital in Southeast Ethiopia, whereas this study was conducted across multiple centers, including hospitals and healthcare centers.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations